Feeding habits and helminth parasites of sardine (S. pilchardus) and anchovy (E. encrasicolus) in the Adriatic Sea - ZORICA, B.; ČIKES KEČ, V.; VIDJAK, O.; MLADINEO, I.; EZGETA BALIČ, D. (Mediterranean Marine Science, 2015)
We examined the stomach contents of two of the most economically and ecologically important small pelagic fish species, the sardine, Sardina pilchardus and the anchovy, Engraulis encrasicolus, obtained monthly from commercial purse-seine catches operating on Croatian fishing grounds during a one-year period (January–December, 2011). Both species generally showed a similar diet, with copepod and decapod larvae as dominant prey groups. The composition of anchovy and sardine stomach contents was not size- or sex-related, but throughout the year, a significant difference in diet composition was observed for each species as well as between species. Two gastrointerstinal helminths; the digenean Parahemiurus merus and nematode Hysterothylacium aduncum, were recorded during the stomach content analysis. Differences in population dynamics between the two parasites are congruent with differences in the prey composition of sardine and anchovy, reflecting fine-tuned interactions in the trophic web between parasites and intermediate or paratenic hosts included in the sardine and anchovy diet.